Qolbun Munib dalam Q.S Qaf Ayat 33 (Studi Komparatif Wahbah az-Zuhaili dengan Mufassir Klasik) - Bahri, Muhammad Ulul (Lembaga Yasin AlSys, 2023)
This research is a qualitative research that is library research, using an interpretation approach, and a comparative interpretation method. The data sources used are primary sources in the form of the holy Qur'an, and secondary sources in the form of commentaries as well as books and literature that are representative of research studies. In this study, the authors found that First, the meaning of Qalbun Munib in QS Qaf verse 33, is the heart of someone who returns to Allah with full repentance because his heart is always filled with fear of the majesty of his Lord and tries his best to leave his own lusts. Second, the stages in reaching Qolbun Munib include: Renewing Repentance, Restraining Lust, Fear of Al-Rahman (God the Most Merciful), Maintaining the Rules and Shari'ats of Allah, Husnu Dzhan to Allah . Third, the meaning of Qolbun Munib according to Prof. Dr. Wahbah Az-Zuhaili with classic Mufassir (Shaykh Imam Al-Qurthubi, Shaykh Imam Abu Ja'far Muhammad Jarir Ath-Tabari, Imam Ibnu Katsir, and Imam Jalaluddin Al-Mahalli). With this research, the authors hope to add to the body of knowledge for readers, especially the researchers themselves related to the object of study. In addition, with this thesis, readers or whoever it is can apply things that would be useful in this thesis in everyday life.